Metadata Reference Model for IPS2 Lifecycle Management - Abramovici, M.; Neubach, M.; Schulze, M.; Spura, C. (Cranfield University Press, 2009)
Metadata models are the nucleus of product data and lifecycle management. Current PLM solutions offer generic metadata models for physical products and consider only the product provider’s requirements. They are not sufficient to meet the new requirements and have to be extended in order to provide support for industrial product-service system (IPS²). Based on use case analyses, expert interviews and interviews with participants of the research project the different requirements of IPS2 providers and customers are identified and a proposal for a metadata reference model for IPS2 lifecycle management is introduced. This metadata model provides the foundation not only for basic PLM methods but also for advanced IPS2 management methods like IPS2 change management, IPS2 customer feedback management and IPS2 executive information management. The IPS² metadata reference model could be the basis for further standardisation activities.
Organised by: Cranfield University
Keywords: IPS2; Lifecycle Management; Metadata Reference Model